Deficient endoplasmic reticulum translocon‐associated protein complex limits the biosynthesis of proinsulin and insulin. Issue 5 (3rd April 2021) - Huang, Yumeng; Xu, Xiaoxi; Arvan, Peter; Liu, Ming
Abstract: The conserved endoplasmic reticulum (ER) membrane protein TRAPα (translocon‐associated protein, also known as signal sequence receptor 1, SSR1) has been reported to play a critical but unclear role in insulin biosynthesis. TRAPα/SSR1 is one component of a four‐protein complex including TRAPβ/SSR2, TRAPγ/SSR3, and TRAPδ/SSR4. The TRAP complex topologically has a small exposure on the cytosolic side of the ER via its TRAPγ/SSR3 subunit, whereas TRAPβ/SSR2 and TRAPδ/SSR4 function along with TRAPα/SSR1 largely on the luminal side of the ER membrane. Here, we have examined pancreatic β‐cells with deficient expression of either TRAPβ/SSR2 or TRAPδ/SSR4, which does not perturb mRNA expression levels of other TRAP subunits, or insulin mRNA. However, deficient protein expression of TRAPβ/SSR2 and, to a lesser degree, TRAPδ/SSR4, diminishes the protein levels of other TRAP subunits, concomitant with deficient steady‐state levels of proinsulin and insulin. Deficient TRAPβ/SSR2 or TRAPδ/SSR4 is not associated with any apparent defect of exocytotic mechanism but rather by a decreased abundance of the proinsulin and insulin that accompanies glucose‐stimulated secretion. Amino acid pulse labeling directly establishes that much of the steady‐state deficiency of intracellular proinsulin can be accounted for by diminished proinsulin biosynthesis, observed in a pulse‐labeling as short as 5 minutes. The proinsulin and insulin levels in TRAPβ/SSR2 or TRAPδ/SSR4 null mutant β‐cells are notably recovered upon re‐expression of the missing TRAP subunit, accompanying a rebound of proinsulin biosynthesis. Remarkably, overexpression of TRAPα/SSR1 can also suppress defects in β‐cells with diminished expression of TRAPβ/SSR2, strongly suggesting that TRAPβ/SSR2 is needed to support TRAPα/SSR1 function.